Statistical signal analysis of the gas quality intelligence system - Швейкін, Олександр Леонідович; Прокопенко, Олена Олександрівна (Technology audit and production reserves, 2014)
The factor analysis of the measuring system was conducted in the paper. In particular, the descriptive statistics, correlation matrix, factor matrix and its geometrical interpretation were obtained. The visual structure of factors, affecting the measurement process was obtained. The analysis allowed to select two almost independent factors. Strongly correlated variables were combined in factors. It turned out that it was enough to investigate the influence of two factors to reflect the relations between six system variables and describe the object. They reproduce information on observation results with the accuracy, sufficient for practical purposes. The first factor affects the temperature modes of system elements and indicators, reflecting them. The second affects the pressure values in the system constriction device. The correctness of natural gas quality indicators investigation, performed in the measuring system by studying the influence of these two factors was proved.